EKSISTENSI SENI HIAS RUMAH TRADISIONAL KUDUS - Arif Suharson; Dharsono Dharsono; Bambang Sunarto; Nanik Sri Prihatin (Corak : Jurnal Seni Kriya, 2021)
This study aims to understand the existence of Kudus traditional house decorative art that is formed in conjunction with the culture that enters the cultural life of the Kudus people. The presence of decorative art has an important meaning for the community because it is closely related to the noble values that become a learning vehicle for the next generation. Decorative art in Kudus traditional house made with a variety of decorative diversity that is behind it is a form of strong cultural perspective. The decorative art is deliberately made to have beautiful forms of stilisasi, magnificent but also related to the meaning of symbols. Grounded research with three steps of activity simultaneously, namely:  data reduction, data presentation, and verification or withdrawal of conclusions with inter-pretative model analysis conducted to produce valid research. As a result of human culture, the phenomenon of artifacts is certainly inseparable from the sociocultural context in art. The decorative art of Kudus traditional house characterized by coastal culture was born with the strengthening of socio-economic progress of the community with the concept of "gusjigang" “bagus, ngaji, and dagang” that upholds the values of teachings in Islam.Penelitian ini memiliki tujuan untuk memahami eksistensi seni hias rumah tradisional Kudus yang terbentuk bersamaan dengan budaya yang masuk dalam kehidupan budaya masyarakat Kudus. Kehadiran seni hias memiliki arti penting bagi masyarakat karena berkaitan erat dengan nilai-nilai luhur yang menjadi wahana pembelajaran bagi generasi penerusnya. Seni hias pada rumah tradisional Kudus yang dibuat dengan keberagaman ragam hias yang melatarbelakanginya merupakan wujud perspektif budaya yang kuat. Seni hiasnya sengaja dibuat agar memiliki bentuk-bentuk stilasi yang indah, megah, tetapi juga berkaitan dengan makna simbol. Pendekatan grounded research dengan tiga langkah kegiatan secara bersamaan, yaitu: reduksi data, penyajian data, dan verifikasi atau penarikan simpulan dengan  analisis model interpretatif dilakukan untuk menghasilkan penelitian yang valid. Sebagai hasil kebudayaan manusia, fenomena artefak ini sudah barang tentu tidak dapat dipisahkan dari konteks sosiokultural dalam berkeseniannya. Seni hias rumah tradisioal Kudus yang bercirikan budaya pesisiran lahir dengan menguatnya kemajuan sosial ekonomi masyarakat dengan konsep “gusjigang” “bagus, ngaji, dan dagang” yang memegang teguh nilai-nilai ajaran dalam agama Islam.